USING PICTURE BOOKS AND ILLUSTRATED STORIES TO TEACH ENGLISH VOCABULARY - Abdiqayumova Mohinur Zohid qizi; Gazieva Saida Turgunovna (NAZARIY VA AMALIY FANLARDAGI USTUVOR ISLOHOTLAR VA ZAMONAVIY TA’LIMNING INNOVATSION YO’NALISHLARI, 2025)
The article speaks about the effective use of picture books and illustrated stories as a tool for teaching English vocabulary, particularly to beginners and children. It states the greatest benefits of using visual aids in language learning, emphasizing how illustrations and contextual cues in books help children connect unknown words with meanings. The article discusses various means of integrating picture books into vocabulary lessons, including using them to introduce thematic vocabulary, reinforce concepts, and engage students in interactive activities. The article also deals with the use of storytelling as a vehicle for building language comprehension and recall, with learning becoming enjoyable and memorable. The article also integrates evidence from education research, which demonstrates that the inclusion of pictures with text strengthens vocabulary acquisition and promotes language learning. With real-life examples and suggestions, this article is a useful tool for teachers wanting to improve their practices and develop a more interesting and successful English language learning process.